THE RELATIONSHIP BETWEEN MOTHERS' KNOWLEDGE ABOUT FEEDING PATTERNS AND THE NUTRITIONAL STATUS OF TODDLERS - Media Fitri; Yessi Pertiwi; Fiona Fani (IKES Payung Negeri Pekanbaru, 2025)
Rapid growth and development occur during infancy. This growth and development must be supported by adequate daily nutritional intake. Failure to do so can have long-term consequences. The purpose of this study was to determine the relationship between maternal knowledge about feeding patterns and the nutritional status of toddlers aged 12-59 months. This study used a descriptive correlational design with a cross-sectional approach, with a sample size of 48 respondents. The results of the univariate analysis showed that most toddlers had good nutrition and most mothers had good knowledge about feeding patterns. Thus, there was a significant relationship between maternal knowledge about feeding patterns and nutritional status in toddlers at RSI Bukittinggi. It is recommended that health workers improve maternal knowledge about feeding patterns for toddlers to ensure their nutritional needs are met.